Comparative analysis of a conventional cantilever abutment and innovative double abutment in dental implant prosthesis: A finite element analysis study - Luciana Silva Colepícolo; Paulo Henrique Vieira Magalhães; Maria Auxiliadora Mourão Martinez; Luís Otávio Miranda Cota; Rafael Paschoal Esteves Lima; Lucas Fernandes Sousa Pessoa; Guilherme Augusto Oliveira; Fernando Oliveira Costa (Biomedical Engineering Advances)
The innovative double paraboloid abutment (DA) in dental implant prosthesis is based on the new concept of Biodynamic Optimized Peri-implant Tissue (BOiT) and was introduced in a human case series report with follow-ups ranging from 3 to 12 years. This study aimed to evaluate the influence of two structural designs: the innovative DA and a distal conventional cantilever (CC) in fixed prostheses retained by a single dental implant. The evaluation focused on stress and strain distributions in bone tissue (cortical and medullary), as well as stress distribution in the abutments, UCLA, implants, and retaining screws under axial and oblique loading, using 3D finite element analysis. Each model consisted of a bone block representing the area from the right second premolar to the first molar, with one internal hexagon implant (4.0 × 10 mm) supporting a fixed dental prosthesis of two elements. Forces of 100 N were applied in both axial and oblique directions (at 30° in the Y direction). The von Mises criterion was used to assess maximum principal stress values and microstrain. Simulations were created using ANSYS mechanical software. After applying the loads and obtaining the stress results, using the same materials for each of the modeled parts, as well as bone and identical loads, it was observed that the DA design yielded more favorable results than the cantilever. The DA showed significantly lower stress levels and better strain distributions, indicating a more favorable biomechanical interaction between structures. These findings suggest that DA designs may reduce stress concentrations and potentially minimize the risk of clinical complications compared to traditional CC designs, leading to improved long-term implant stability and success rates in patients missing two adjacent dental elements, supported by a single osseointegrated implant.